Benign Juvenile Melanoma in An 8-Year-Old Boy - Cáceres, Héctor (1996)
Juvenile melanoma or Spitz's nevus is a rare form of benign melanocytic nevus that may be easily confused with both, a true malignant melanoma or vascular lesions capillary hemangiomas like. A case of an 8-year-old boy with a Spitz's nevus on his nasal lobe since the age of one year is presented; diagnosis and treatment of immature capillary hemangioma was performed. Histopathologic study showed ephitelioid melanocytic cells without atypia signs. Surgical excision of lesion was done, with succesful esthetic results.